Predicted asteroseismic detection yield for solar-like oscillating stars with PLATO - Goupil M.J.; Catala C.; Samadi R.; Belkacem K.; Ouazzani R.M.; Reese D.R.; Appourchaux T.; Mathur S.; Cabrera J.; Börner A.; Paproth C.; Moedas N.; Verma K.; Lebreton Y.; Deal M.; Ballot J.; Chaplin W.J.; Christensen-Dalsgaard J.; Cunha M.; Lanza A.F.; Miglio A.; Morel T.; Serenelli A.; Mosser B.; Creevey O.; Moya A.; Garcia R.A.; Nielsen M.B.; Hatt E. (My University, 2025)
Aims. In this work, we determine the expected yield of detections of solar-like oscillations for the targets of the foreseen PLATO ESA mission. Our estimates are based on a study of the detection probability, which takes into account the properties of the target stars, using the information available in the PIC 1.1.0, including the current best estimate of the signal-to-noise ratio (S/N). The stellar samples, as defined for this mission, include those with the lowest noise level (P1 and P2 samples) and the P5 sample, which has a higher noise level. For the P1 and P2 samples, the S/N is high enough (by construction) that we can assume that the individual mode frequencies can be measured. For these stars, we estimate the expected uncertainties in mass, radius, and age due to statistical errors induced by uncertainties from the observations only. Methods. We used a formulation from the literature to calculate the detection probability. We validated this formulation and the underlying assumptions with Kepler data. Once validated, we applied this approach to the PLATO samples. Using again Kepler data as a calibration set, we also derived relations to estimate the uncertainties of seismically inferred stellar mass, radius, and age. We then applied those relations to the main sequence stars with masses equal to or below 1.2 M belonging to the PLATO P1 and P2 samples and for which we predict a positive seismic detection. Results. We found that we can expect positive detections of solar-like oscillations for more than 15 000 FGK stars in one single field after a twoyear observation run. Among them, 1131 main sequence stars with masses of 1:2 M satisfy the PLATO requirements for the uncertainties of the seismically inferred stellar masses, radii, and ages. The baseline observation programme of PLATO consists of observing two fields of similar size (one in the southern hemisphere and one in the northern hemisphere) for two years apiece. Accordingly, the expected seismic yields of the mission amount to over 30 000 FGK dwarfs and subgiants, with positive detections of solar-like oscillations. This sample of expected solar-like oscillating stars is large enough to enable the PLATO mission's stellar objectives to be amply satisfied. Conclusions. The PLATO mission is expected to produce a catalog sample of extremely well seismically characterized stars of a quality that is equivalent to the Kepler Legacy sample, but containing a number that is about 80 times greater, when observing two PLATO fields for two years apiece. These stars are a gold mine that will make it possible to make significant advances in stellar modelling. © 2024 EDP Sciences. All rights reserved.